Analysis of the hyperfine structure of the 13Δg, 23Πg, and 33Σg+ states of 6Li7Li. (August 2021) - Onishchenko, Sofiia S.; Sovkov, Vladimir B.; Xie, Feng; Li, Dan; Lukashov, Sergey S.; Baturo, Vera V.; Wu, Jizhou; Ma, Jie
Highlights: We theoretically examine the isotope-substituted homonuclear molecule and present how our approach is applied to this case. The effective Hamiltonian of the molecular system and the main stages of the computational algorithm are revealed. We demonstrate simulations of the experimental spectra and estimate the parameters responsible for the hyperfine splitting. We estimate the asymptotic behavior of the Fermi contact interaction and compare it with values obtained in the optimization. Abstract: We report on our theoretical analysis of the hyperfine splitting in the spectra of the 1 3 Δ g, 2 3 Π g, and 3 3 Σ g + triplet states of 6 Li 7 Li, which were experimentally observed in 2002 (Li et al.) by means of Perturbation Facilitated Optical-Optical Double Resonance (PFOODR) spectroscopy. In our previous work, both homonuclear and heteronuclear molecules were analyzed. However, in this work, we theoretically investigate an isotope-substituted homonuclear molecule for the first time and demonstrate the application of our approach to this case. In our model, we reproduce the major stages of the excitation–de-excitation schemes by considering the mixed nature of the intermediate A 1 Σ u + ∼ b 3 Π Ω u singlet–triplet states, whereby the three components of the Ω = 0, 1, 2 basis states might contribute to the hyperfine splitting. We compute the contributions from all components of the mixed states. We present physical models for all triplet states under study, along with the obtained parameters of the analyzed molecular system and the simulation results. Additionally, we describe the principal steps of the computational algorithm in detail.